Implementation of Play-Based Learning in Developing Social-Emotional Skills of 5–6-Year-Old Children in Integrated Islamic Kindergarten - Aisyah, Aisyah; Hakim, Arif Rohman (Generasi, 2025)
Backround: Social-emotional competencies developed during early childhood significantly influence lifelong learning and well-being. Play-based learning offers developmentally appropriate approaches for fostering these competencies, yet implementation in integrated Islamic kindergartens remains underexplored, particularly regarding values integration within child-centered pedagogy.Objective: This research examined the implementation of play-based learning for developing social-emotional competencies among 5–6-year-old children in integrated Islamic kindergartens, including forms and strategies employed, effectiveness across competency domains, Islamic values integration, and facilitating factors and obstacles.Method: Employing a qualitative descriptive-analytical design, the study conducted participant observations, in-depth interviews with eight teachers and two principals, focus group discussions, and documentation analysis across two purposively selected integrated Islamic kindergartens over twelve weeks. Data analysis followed Miles, Huberman, and Saldaña's interactive model. Three play forms—free play, guided play, and structured play—were systematically implemented, with guided play predominating (62% of observed activities).Findings and Implications: All five social-emotional competency domains showed substantial development: self-awareness (78% improvement in emotional vocabulary use), self-management (85% increase in conflict resolution without teacher intervention), social awareness (92% demonstrated perspective-taking behaviors), relationship skills (88% engaged in sustained cooperative play), and responsible decision-making (73% applied problem-solving strategies independently).Conclusion: Islamic values were successfully integrated through environmental design, activity content, and teacher-child interactions without compromising developmental appropriateness. Teacher competency and administrative support emerged as critical facilitating factors, while time constraints and parent misconceptions presented persistent challenges. Play-based learning effectively develops social-emotional competencies in young children when implemented with intentionality, adequate support, and cultural responsiveness, demonstrating compatibility between faith-based character education and child-centered pedagogy.